1986
DOI: 10.1002/bit.260280503
|View full text |Cite
|
Sign up to set email alerts
|

Continuous hybridoma growth and monoclonal antibody production in hollow fiber reactors–separators

Abstract: Growth of a hybridoma culture, along with production of monoclonal antibody, was demonstrated over extended periods in polysulfone hollow fiber membrane modules. The molecular weight cutoffs of the membranes were 70,000, 50,000, and 100,000 daltons. The hybridoma cell line, designated 65/26, produced IgG (2b/kappa) directed at mouse thymus cell surface antigen, TL.1. Cell growth occurred in the shell space of the reactor, using supplemented RPMI 1640 (20% fetal bovine serum) supplied from a separate reservoir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(35 citation statements)
references
References 15 publications
0
35
0
Order By: Relevance
“…Purity of the antibody product has been facilitated by gradual serum reduction in the culture medium which has been achieved in hollow fiber systems without significant inhibitory effect on production (42,45,46,50,51).…”
Section: Schematic Diagram Of a Hollow Fiber Bioreactormentioning
confidence: 99%
See 2 more Smart Citations
“…Purity of the antibody product has been facilitated by gradual serum reduction in the culture medium which has been achieved in hollow fiber systems without significant inhibitory effect on production (42,45,46,50,51).…”
Section: Schematic Diagram Of a Hollow Fiber Bioreactormentioning
confidence: 99%
“…Use of microporous hollow fiber bioreactors with large fiber pore sizes, between 0.2 and 0.5 p, have been described (26,32,51,52). In comparison to ultrafiltration membranes, greater antibody production has been achieved with these microporous membranes (26,52), however the product is not retained within the small volume of the extracapillary space and must be concentrated from the large volume of perfusing media.…”
Section: Schematic Diagram Of a Hollow Fiber Bioreactormentioning
confidence: 99%
See 1 more Smart Citation
“…The few reports that are available on the relationship between the cell cycle and monoclonal antibody synthesis suggest that the relationship is cell line dependent. Alshuler et al (1986) reported the detection of intracellular antibody throughout the cell cycle in mouse hybridomas while Al-Rubeai et al (1989) claimed production was G l phase-specific. Suzuki and Ollis (1989) proposed a cell cycle model based on experimental evidence which showed that antibody production was restricted to the late G l and S phases.…”
Section: Stress and Monoclonal Antibody Productionmentioning
confidence: 99%
“…Although several novel continuous bioreactors have been developed for the culture of suspended mammalian cells (1)(2)(3)(4)(5)(6)(7)(8)(9), conventional roller bottles still provide the simplest means for culturing suspended mammalian cells that are shearsensitive but still require some means of agitation for cell suspension and oxygen and nutrient dispersion. Although each novel bioreactor has its own advantages, such as improvements in cell density, viability percentages, monoclonal antibody secretion rates, etc., these systems are generally not as mechanically simple or as easily scaleable as are roller bottles, require special user training, and require capital investment.…”
Section: Introductionmentioning
confidence: 99%